Cementoblastoma Relating to Right Mandibular Second Primary Molar - Sivakumar Nuvvula; Swapna Manepalli; Abinash Mohapatra; Sreekanth Kumar Mallineni (Hindawi Limited, 2016)
Cementoblastoma is a benign lesion of the odontogenic ectomesenchymal origin. It rarely occurs in primary dentition. This report describes a case of a cementoblastoma relating to the right mandibular second primary molar in a 7-year-old girl. Her panoramic radiograph revealed a well-defined radiopaque lesion with a radiolucent border extending from the distal surface of the mandibular right first primary molar to the distal surface of mandibular second primary molar. The tumor was attached to the mesial root of primary second molar and was excised along with the teeth involved and sent for histopathological evaluation, which showed irregular trabeculae of mineralized tissue interspersed with fibrovascular connective tissue, trabeculae of mineralized tissue with prominent reversal lines, and peripheral rimming of the mineralized tissue with blast cells. On a six-month follow-up, there has been no recurrence of the lesion.